Effects of melatonin, proline, and salicylic acid on seedling growth, photosynthetic activity, and leaf nutrients of sorghum under salt stress - Mehmet Sait Kiremit; Elif Öztürk; Hakan Arslan; Bhaskara Anggarda Gathot Subrata; Hasan Akay; Aigerim Bakirova (Plant Direct, 2024)
Abstract Soil salinization poses a significant challenge to the sustainability and productivity of agriculture worldwide. This issue continues to hinder plant growth, requiring innovative solutions to alleviate salt stress. Moreover, climate change accelerates soil salinization, which may soon spread to previously unaffected agricultural areas. Therefore, the present study evaluated the potential role of different seed priming agents (hydro (H), salicylic acid (SA), proline (P), and melatonin (MEL)) on seedlings and leaf macro and micronutrients of sorghum grown under four (.27, 2.5, 5.0, and 8.0 dS m−1) soil salinity conditions. Soil salinity drastically reduced all the growth parameters of sorghum seedlings, primarily the reduction in growth traits, which was remarkable after 2.5 dS m−1 soil salinity. In addition, plant height, shoot fresh weight, and stomata were reduced by 40.8%, 74.6%, and 36.5%, respectively, at 8.0 dS m−1 compared to .27 dS m−1. SA‐ and MEL‐primed seeds mitigated the harmful effects of soil salinity by reducing Na+ accumulation in the leaves and increasing the K+/Na+ and Ca2+/Na+ ratios and photosynthetic activity under salt stress. However, the Zn2+, Mn2+, and Cu2+ contents of sorghum leaves increased with increasing soil salinity, and these nutrients also improved with seed priming by SA, MEL, and P. Considering all nutrients, MEL‐primed sorghum seeds had better macro‐ and micro‐nutrient uptake capacities than the H, SA, and P treatments under high soil salinity conditions. Finally, the present study showed that MEL‐induced improvement in salt tolerance in sorghum seedlings was related to enhanced nutritional status, photosynthetic activity, and biomass production in salinized areas.